Humanising migrant women's work. (May 2017) - Rydzik, Agnieszka; Pritchard, Annette; Morgan, Nigel; Sedgley, Diane
Highlights: Gives insight into female migrant tourism worker experiences and their long-term career trajectories. Demonstrates the methodological potential of 'one voice' research. Challenges gender-blind, homogenising accounts of migrant tourism workers. Demonstrates female migrant tourism workers' intersectional marginalisation. Reveals migrant employee resistance and empowerment. Abstract: Female migrants make an important contribution to the global tourism industry yet their employment experiences and histories are poorly understood. This paper draws on a phenomenological position to explore the life-world and ten-year employment trajectory of one highly skilled Polish immigrant to the UK as told through her own voice and artwork. It challenges prevailing de-personalised and gender-blind accounts of tourism migrant workers, and demonstrates the methodological potential of one-voice research to humanise the female migrant experience, document long-term employment trajectories and foreground complex working lives. The paper provides nuanced understanding of intersectional gendered and ethnic marginalisation in the labour market and explores the ways in which employment creates spaces for both oppression and self-determination for precarious workers.